In Utero Gene Therapy (IUGT) Using GLOBE Lentiviral Vector Phenotypically Corrects the Heterozygous Humanised Mouse Model and Its Progress Can Be Monitored Using MRI Techniques - Shangaris, Panicos (Sci Rep, 2019)
In utero gene therapy (IUGT) to the fetal hematopoietic compartment could be used to treat congenital blood disorders such as β-thalassemia. A humanised mouse model of β-thalassemia was used, in which heterozygous animals are anaemic with splenomegaly and extramedullary hematopoiesis. Intrahepatic in utero injections of a β globin-expressing lentiviral vector (GLOBE), were performed in fetuses at E13.5 of gestation. We analysed animals at 12 and 32 weeks of age, for vector copy number in bone marrow, peripheral blood liver and spleen and we performed integration site analysis. Compared to noninjected heterozygous animals IUGT normalised blood haemoglobin levels and spleen weight. Integration site analysis showed polyclonality. The left ventricular ejection fraction measured using magnetic resonance imaging (MRI) in treated heterozygous animals was similar to that of normal non-β-thalassemic mice but significantly higher than untreated heterozygous thalassemia mice suggesting that IUGT ameliorated poor cardiac function. GLOBE LV-mediated IUGT normalised the haematological and anatomical phenotype in a heterozygous humanised model of β-thalassemia.